Figurative Language An Analysis of Figurative Language Used in William Shakespeare’s Poems: Figurative language; Poem; William Shakespeare - Rustandi, Encep (ELATICS JOURNAL, 2023)
Poem is one of the popular literary works that is loved by many people because of its beautiful language and the deep meaning of it. In poem, there are words or sentences that has a poetic meaning. Many poets write poems that have hidden or unreal meanings in it, and it is called figurative language. With figurative language applied in the poem, some people do not understand what the idea behind it. Therefore, this research aimed is to analyze the type of figurative language used in William Shakespeare’s poems and to reveal the function of figurative language dominantly used in William Shakespeare’s poems. The titles of the 7 William Shakespeare’s poems were “Shall I Compare Thee to A Summer’s Day?”, “Let Me Not to The Marriage of True Minds”, “Like as The Waves Make Towards the Pebbled Shore”, “When, In Disgrace with Fortune and Men’s Eyes”, “All the World’s Stage”, “That time of year thou mayst in me behold”, and “The Rape of Lucrece”. Results showed six types of figurative language used in William Shakespeare’s